Blockchain-based battery energy storage systems for mitigating solar intermittency - Teo, Jing (Nanyang Technological University, 2022)
As one of the widely used distributed generation energy sources in Singapore, solar photovoltaic is an important aspect of the increased use of renewable energy. However, the power generation profile of solar photovoltaic is vulnerable to the effects of Singapore’s weather conditions which causes intermittencies to occur during power generation. One solution is the use of a battery energy storage system to reduce intermittency. With the storage of excess energy, consumers could trade their excess energy with each other within the microgrid. Recently, the soaring popularity of Blockchain technology has led to its development and maturity. The smart contract mechanism of Blockchain technology could be used to conduct peer-to-peer energy trading between consumers in the microgrid due to its convenience, efficiency and relative safety. The pricing scheme of energy trading will be written using a smart contract to be executed automatically.